Simulation of MinD pattern formation in escherichia coli in the absence of MinE / Shamsidar Sopie - Shamsidar, Sopie (2011)
In Escherichia coli, the Z ring has the potential to assemble anywhere along the cell length but is restricted to midcell by the action of negative regulatory systems, including Min. In the current model for the Min system, the MinC/MinD division inhibitory complex is evenly distributed on the membrane and can disrupt Z rings anywhere in the cell; however, MinE spatially regulates MinC/MinD by restricting it to the cell poles, thus allowing Z rings formation at midcell. This model assumes that Z rings, formed at different cellular locations have equal sensiticity to MinC/MinD in the absence of MinE. However, there is evidence reported that differences in MinC/MinD sensitivity between polar and internal Z rings exists even when there is no MinE. MinC/MinD alone at proper levels is able to block minicell production. This computational research focused on optimization on reaction and diffusion rate that simulate the new experimentally proposed model in differences in MinC/MinD sensitivity between polar and non polar Z rings in Escherichia coli. In this proposed system, MinE are discarded from the system to imitate the lacking of MinE in the FtsZ-I374V strain in vivo. The result produced patches that is assumed to stay at poles forever so that inhibition of FtsZ can occur, thus lead to the formation of Z rings at midcell. This in silico research will provide significant information and better understanding on the reaction and diffusion rate that affect the oscillation of Min proteins without the presence of MinE Future work will focus on the simulation in triangular environment that was predicted to provide more sharply curved membrane that make able to the patches to localize at poles.